Effects of fat source and level in finishing pigs and increasing omega-3 fatty acids in nursery pigs - Bromm, Jenna Joyce (Kansas State University, 2022)
This thesis includes two chapters evaluating practical questions facing the swine industry including the effects of fat source and level in finishing pig diets and the evaluation of increasing levels of omega-3 fatty acids in nursery pig diets. Two experiments using a total of 3,4171 finishing pigs were used to evaluate the effects of different fat sources and levels on growth performance, carcass characteristics, and economical return. In Experiment 1, three of the four dietary treatments contained increasing levels of choice white grease (0, 1, and 3% of the diet). The final dietary treatment contained no added fat until pigs were approximately 100 kg, then pigs were fed a diet containing 3% added fat. Results from this experiment determined that increasing fat from 0 to 3% decreased ADFI and improved G:F. Pigs fed 3% added fat only during the late finishing phase had intermediate G:F. Increasing fat increased feed cost and reduced income over feed cost. With 3% added fat fed only in late finishing, feed costs and IOFC were intermediate between diets containing 0% added fat and 3% fat added throughout the entire study. Dietary treatments for Experiment 2 included a control diet containing no added fat. The other 4 dietary treatments included two different fat sources, choice white grease or corn oil, added at 1 or 3% of the diet. Results from this experiment concluded that increasing fat from 0 to 3% increased ADG, reduced ADFI, and improved G:F, regardless of fat source used. Increasing fat also increased HCW, carcass yield, and backfat, while pigs fed diets containing corn oil, had higher carcass fat iodine values. Increasing fat increased feed cost, but also increased revenue. However, increasing fat only increased income over feed cost when feed costs were low and revenue was high. Three experiments were conducted using a total of 92,546 nursery pigs to assess the effects of increasing omega-3 fatty acids (alpha-linolenic acid from O3 Trial Feed) on nursery pig growth performance, response to an LPS immune challenge, and morbidity and mortality in PRRSV positive pigs in a commercial setting. In Experiment 3, increasing omega-3 fatty acids did not improve growth performance or immune response induced by LPS challenge. In Experiment 4, increasing omega-3 fatty acids improved growth performance and reduced total removals and mortality in PRRSV positive pigs. However, in experiment 5 increasing omega-3 fatty acids in the diet did not improve growth performance and actually increased total removals and mortality in PRRSV positive pigs. In summary, these experiments provided data on different fat sources and levels in fishing pig diets and increasing omega-3 fatty acids in nursery pig diets.
Keywords: Fat; Finishing pig; Omega-3; Nursery pig; PRRSV; LPS